Differentiating Progressive Supranuclear Palsy and Parkinson's Disease With Head-Mounted Displays - Herwig, Arvid; Agic, Almedin; Huppertz, Hans-Jürgen; Klingebiel, Randolf; Zuhorn, Frédéric; Schneider, Werner X.; Schäbitz, Wolf-Rüdiger; Rogalewski, Andreas (Frontiers in Neurology, 2021)
Background: Progressive supranuclear palsy (PSP) is a neurodegenerative disorder that, especially in early stages of disease, is clinically difficult to distinguish from Parkinson’s disease (PD). Objective: This study aimed at assessing the use of eye-tracking in head mounted displays for differentiating PSP and PD. Methods: Saccadic eye movements of 13 patients with PSP, 15 patients with PD and a group of 16 healthy controls (HCs) were measured. To improve applicability in an inpatient setting and standardize the diagnosis all tests were conducted in a head-mounted display. In addition, patients underwent atlas-based volumetric analysis of various brain regions based on high-resolution magnetic resonance imaging. Results: Patients with PSP displayed unique abnormalities in vertical saccade velocity and saccade gain, while horizontal saccades were less affected. A novel diagnostic index was derived, multiplying the ratios of vertical to horizontal gain and velocity, allowing a segregation of PSP from PD with high sensitivity (10/13, 77%) and specificity (14/15, 93%). As expected, patients with PSP as compared to PD patients showed regional atrophy in midbrain volume, the midbrain plane, and the midbrain tegmentum plane. Additionally, we found for the first time that oculomotor measures (vertical gain, velocity and the diagnostic index) were correlated significantly to midbrain volume in the PSP group. Conclusions: Assessing eye movements in a head-mounted display provides an easy to apply and highly standardized tool to differentiate patients PSP from PD and HCs, which will aid in the diagnosis of PSP.